(untitled) (Research, Society and Development, 2023)
Celiac disease is a common alteration, being related to gluten, we have varied symptoms. Thus, it is recommended that celiac patients maintain a diet restricted in foods containing gluten, such as wheat, rye and barley. It is noted that many patients use a gluten-free diet without professional supervision, making them susceptible to the development of certain deficiencies, such as hypovitaminosis B, D, calcium, iron and folic acid. Therefore, alternative foods that may contribute to reducing the inflammatory aspects associated with celiac disease have been proposed. The objective of this study, therefore, was to carry out a narrative review covering the epidemiology of celiac disease in Brazil and in the world, as well as the use of turmeric as a relevant treatment due to combating and alleviating the inflammatory symptoms caused by celiac disease. “PubMed” and “Google Academic” databases were used, selecting articles published in the language, preferably in English, between the years 2008 and 2022, with the descriptors: “antioxidant; turmeric”; “celiac disease”; “microbiota” and “intestinal inflammation diseases”. Initially, 108 articles were identified, with an increasing number of publications between 2015 and 2022 and, after careful reading, 13 articles were selected. It is inferred, based on the presented literature, that the development of therapeutic alternatives such as turmeric, to help in the treatment of celiac disease, is still incipient, with the need for further studies, in the short and long term, on the effects of these products. in the inflammatory processes caused by the ingestion of gluten by celiac patients.